The Mediating Effect of On the Job Training for Work Ability on Productivity Improvement Politeknik Matra Udara’s Cadets - Gumilar, Bagja; Hariadi, Eko; Agung, Achmad Imam (Technium Social Sciences Journal, 2024)
The primary goal of this study is to analyze the impact of work performance on productivity and to analyze the role of on-the-job training (OJT) variables in mediating independent variables against dependent variables at Politeknik Matra Udara. The process of gathering data influences the researcher's decision to provide the questionnaire to the respondent. This study uses a quantitative approach, using structural equation modeling (SEM) for analysis, and utilizes the Smart-PLS statistical tool. Using a 5% significance level, the research sample examines the tables Isaac and Michael. The sample of this study consisted of 115 employees from various departments in the airport electrical division of Politeknik Matra Udara who had completed the on-the-job training (OJT) program. The analysis's findings indicate that positive work-related behavior has a significant impact on tardiness productivity. This indicates that when an individual's work performance increases, so does their productivity. In conclusion, on-the-job training, or OJT, has been shown to be a significant mediator in the relationship between work performance and turnover productivity. This indicates that on-the-job training has a critical role in increasing productivity.